Pelatihan Pelayanan Bermutu pada Klinik Kecantikan yang Natural dan Beautyxpert - Harry Nenobais; Yunita Sari; Ferid Nugroho; Roy Tumpal Pakpahan; Muhammad Hanan Rahmadi; Jubery Marwan; Dwi Satriany Unwidjaja; Faridah Ismiyati; Arief Rahman Hakim; Witarlina Zhai (Universitas Prof. Dr. Moestopo (Beragama), 2026)
The goal of business is to create customers. A company's ability to stay in business is a function of its competitiveness and ability to attract customers in a competitive market. Therefore, it is very important for all of us involved in the business world, whether as owners, managers, or employees, to be able to provide the best quality service to our customers so that they are satisfied and remain loyal to the products and services we offer. It is through our customers that our business activities can continue to run optimally and generate maximum profits. The purpose of quality service training for your business is to improve the knowledge, skills, and performance of employees in providing quality service to customers. The methods used in quality service training for your business are surveys, forum group discussion, quality service training, quality service technique mentoring and professional work etiquette, as well as evaluation. The results of the training show that participants' knowledge and skills regarding quality service have increased. Participants realize the importance of creating quality service and professional work etiquette so that customers can be satisfied and loyal.